PERIODE WAKTU PEMBERIAN DAN JENIS PAKAN BERBEDA UNTUK MENINGKATKAN KELANGSUNGAN HIDUP DAN PERTUMBUHAN LARVA IKAN TAMBAKAN (Helostoma temminckii C.V) - Herlina Agustina; Yulisma .; Mirna Fitrani (Jurnal Akuakultur Rawa Indonesia, 2015)
ABSTRACT The aim of this research was to determine the feeding period Artemia sp. nauplii, Moinasp., Tubifex sp., and artificial feed to increasesurvival and growth of kissing gouramy larvae since4th day until 35th after hatching. The research was conducted on July up toSeptember 2014 at Aquaculture Program Study, Agriculture Faculty Sriwijaya University.The research was designed based on Complete RandomizedDesignwith 5 treatments and 3 replications. Larvae (4th day after hatching) were fed four times a day at 08.00 am, 11.00 am, 02.00 pm, and05.00 pm. The treatmentswere larvae that were fed withArtemiasp. nauplii at the age of larvae of 4-15 days, Moina sp.at the age of larvae 14 – 24 days, and Tubifex sp. at the age of larvae 23 – 35 days (P1), Artemiasp. nauplii was gave at age of larvae 4 – 13 days, Moina sp.was gave atage of larvae 12 – 20 days, and Tubifex sp.was gave at the age of larvae 19-35 days (P2), Artemia sp. nauplii was gave at the age of larvae 4 – 11 days, Moina sp.was gave at the age of larvae 10-16 days, and Tubifex sp.was gave at the age of larvae 15 – 35 days (P3), Artemiasp. nauplii was gave at the age of larvae 4 – 13 days, Moina sp.was gave at the age of larvae 12 – 20 days, and artificial feed was gave at the age of larvae 19-35 days (P4), Artemiasp. nauplii was gave at the age of larvae 4 – 11 days, Moina sp.was gave at age of larvae 10-16 days, and artificial feed was gave at the age of larvae 15 – 35 days (P5).The results showed that the highest percentage of survival rate was P3 (59.33%), there was no significantly different with P4 (55%). P4 have the highest of length and weight growth  (23.57 mm; 306mg). Therefore the best result was P4. Keywords : Feed type, Feeding periods, Kissing gouramy, Survival, Growth